A Decision Support Model Suggestion for Logistics Support Unit in Risky Environment - AĞDAŞ, Mustafa; EROĞLU, Özer (Journal of Economics Bibliography, 2016)
Abstract. Storage facilities have an important role for uninterrupted product/service flow and ensuring continuity in supply chains. Criteria, which will be taken into account for the location of this facilities, and criteria values, can alter in accordance with private or public sector and risk environment as well. Besides logistics costs, transportation opportunities and proximity to the customers, risk based criteria such as terror, sabotage, air strikes, and natural disasters play an important role in order to select facility location. During production flow, Logistics Support Bases (LSB) are the military facilities, which affect firstly operation process positively or negatively and secondly result of the operations, serve in the risk environment. In a specific environment, selection of LSB becomes a Multi-Criteria Decision Making (MCDM) problem for the decision maker. This study aims to determine qualifications which will be used to select the best suitable location of LSB; define the importance value of selected qualifications via DEMATEL method, and select the best location of LSB between alternative places. DEMATEL has used in the determination of criteria values and then VIKOR method has used to select the most appropriate location for LSB in the risk environment. Keywords. Logistics support unit, Risk, Facility location, Multi-criteria decision making, DEMATEL, VIKOR. JEL. D81, R53, C40, C44, D70.